Effect of Various Yakult and Molasses Balances in Fermented Bran Production on Their Quality - Fitri, Deswita Adelia; Hernaman, Iman; Rusmana, Denny (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Rice bran is a by-product of rice milling that can be utilized as a growing medium for microorganisms that can be used as functional feed or feed additives. This study aims to analyze the effect of using molasses and Yakult balance in fermented rice bran on pH value, lactic acid content, dry matter loss, and Fleigh value. The research method used was experimental with a complete randomized design (CRD) with 3 treatments and 6 replicates. The treatments consisted of P0 (1000 g rice bran: 300 g molasses), P1 (1000 g rice bran: 200 g molasses: 100 mL diluted Yakult), P2 (1000 g rice bran: 100 g molasses: 200 mL diluted Yakult). Research data were analyzed using Analysis of Variance (ANOVA) and Duncan's multiple range test. The results showed that the treatment gave a significant effect on pH value, lactic acid content, and Fleigh value (NF), but did not give a significant effect on dry matter shrinkage. Treatment P2 (1000 g rice bran: 100 g molasses: 200 mL diluted Yakult) produced the highest lactic acid content (10.98%) and Fleigh value (147.560) compared to other treatments, but also produced a pH value (5.26) and high dry matter shrinkage (5.99). The results of the study can be concluded that the production of fermented bran in 1000 g can be added molasses as much as 100 g and 200 mL of diluted Yakult.